Context‐dependent effects of large‐wildlife declines on small‐mammal communities in central Kenya. Issue 2 (1st March 2015) - Young, Hillary S.; McCauley, Douglas J.; Dirzo, Rodolfo; Goheen, Jacob R.; Agwanda, Bernard; Brook, Cara; Otárola-Castillo, Erik; Ferguson, Adam W.; Kinyua, Stephen N.; McDonough, Molly M.; Palmer, Todd M.; Pringle, Robert M.; et al.
Abstract : Many species of large wildlife have declined drastically worldwide. These reductions often lead to profound shifts in the ecology of entire communities and ecosystems. However, the effects of these large‐wildlife declines on other taxa likely hinge upon both underlying abiotic properties of these systems and on the types of secondary anthropogenic changes associated with wildlife loss, making impacts difficult to predict. To better understand how these important contextual factors determine the consequences of large‐wildlife declines on other animals in a community, we examined the effects of three common forms of large‐wildlife loss (removal without replacement [using fences], removal followed by replacement with domestic stock, and removal accompanied by crop agricultural use) on small‐mammal abundance, diversity, and community composition, in landscapes that varied in several abiotic attributes (rainfall, soil fertility, land‐use intensity) in central Kenya. We found that small‐mammal communities were indeed heavily impacted by all forms of large‐wildlife decline, showing, on average: (1) higher densities, (2) lower species richness per site, and (3) different species assemblages in sites from which large wildlife were removed. However, the nature and magnitude of these effects were strongly context dependent. Rainfall, type of land‐use change, and the interaction of these two factors were key predictors of both the magnitude and type of responses of small mammals. The strongest effects, particularly abundance responses, tended to be observed in low‐rainfall areas. Whereas isolated wildlife removal primarily led to increased small‐mammal abundance, wildlife removal associated with secondary uses (agriculture, domestic stock) had much more variable effects on abundance and stronger impacts on diversity and composition. Collectively, these results (1) highlight the importance of context in determining the impacts of large‐wildlife decline on small‐mammal communities, (2) emphasize the challenges in extrapolating results from controlled experimental studies to predict the effects of wildlife declines that are accompanied by secondary land‐uses, and (3) suggest that, because of the context‐dependent nature of the responses to large‐wildlife decline, large‐wildlife status alone cannot be reliably used to predict small‐mammal community changes.